Implementation of management of scientific writing learning in class XI - Nasrah, Sayni; Kasmarani, Eci; Rahayu, Ririn (Universitas Malikussaleh, 2021)
The purposes of this study are to describe the implementation of management of scientific writing learning in class XI at the SMA Negeri 1 Dewantara. Implementation of learning management is viewed from several main components, namely (1) lesson planning; (2) the learning implementing process; and (3) learning evalution. The approach uses qualitative, with a qualitative descriptive research type. Data collection techniques are observation (seeing and observing events), interviews (meeting directly with informants), and documentation. The validity of the data is tested by triangulation. The data analysis technique is carried out in stages (1) data reduction (summarizing the core data); (2) data presentation (coding of data that has been reduced); (3) conclusions (concluding the data obtained). The research result shows the following matters. First, the planning of learning to write scientific papers are prepared by the teacher is valued 98,4% and is categorized as very good. Second, the process of implementing learning to write scientific papers are carried out by the teacher is 92,9% and categorized as very good. Third, the evalution of learning to write scientific papers are done by the teacher is 77,7% and categorized as good. Because of that it can be stated that these three processes are related to one another. The integration of the three components will describe the readiness of the teacher before learning, the learning processes is directed, and the assessment (evalution) is accurate and will have an impact on aspects of knowledge, aspects of skills, and aspects of student attitude.